Time-resolved step scan FTIR spectroscopy and DFT investigation on triplet formation in peridinin–chlorophyll-a–protein from Amphidinium carterae at low temperature. Issue 4 (2008) - Mezzetti Mezzetti, Alberto Alberto; Spezia Spezia, Riccardo Riccardo
Abstract : We have used time-resolved step-scan FTIR spectroscopy to investigate the process of triplet formation in the peridinin–chlorophyll- a –protein (PCP) at 100 K. Results have led to the identification of possible marker bands for peridinin (Per) and 3 Per. Band assignment has been carried out performing a DFT investigation on Per, 3 Per and on model molecules. The main spectral feature is a couple of bands at 1746 (negative) and 1719 (positive) cm –1 . The assignment of these two bands to the lactonic C═O of Per in (respectively) its fundamental S0 and triplet T 1 state is based on: (1) comparison with FTIR spectra of isolated Per in literature; (2) good agreement with DFT calculations for Per and 3 Per; (3) the downshift of the band upon triplet formation as predicted by DFT calculations in Per and similar lactonic systems; (4) the kinetic of band disappearance, in agreement with literature data. Another possible band for Per in its fundamental state has been identified at 1523 cm –1 . The results are in overall agreement with a recent step-scan FTIR study on PCP at 298 K (Alexandre et al., Biophys. J . 93 (2007), 2118–2128) even though some small discrepancies emerge, probably related to the different temperature at which experiments were carried out. Further DFT calculations have been performed to rationalise these spectral discrepancies. From a methodological point of view, the work demonstrates the potential of a combined step-scan FTIR/DFT approach in the study of photophysical processes in proteins. Furthermore, it has been shown that, when small differential IR signals are concerned, nagging photothermal effects can interfere and can possibly lead to misleading interpretations.